Direct Polymer Curing: Tailored Graphene Micropatterns by Wafer‐Scale Direct Transfer for Flexible Chemical Sensor Platform (Adv. Mater. 2/2021). Issue 2 (12th January 2021) - Kim, Yeonhoo; Kim, Taehoon; Lee, Jinwoo; Choi, Yong Seok; Moon, Joonhee; Park, Seo Yun; Lee, Tae Hyung; Park, Hoon Kee; Lee, Sol A; Kwon, Min Sang; Byun, Hyung‐Gi; Lee, Jong‐Heun; et al.
Abstract : In article number 2004827, Myoung‐Gyu Lee, Byung Hee Hong, Ho Won Jang, and co‐workers report the transfer of graphene micropatterns onto a large‐scale transparent and flexible substrate using direct polymer curing (DPC) transfer. A sensor array with four sensors using micropatterned graphene channels with noble‐metal decoration provides different sensing information and discriminates chemical species.